What makes a city 'breastfeeding‐friendly'? A scoping review of indicators of a breastfeeding‐friendly city - May Loong Tan; Izz Amirah Mohd Shukri; Jacqueline J. Ho; Elizabeth J. O'Sullivan; Amal Omer‐Salim; Fionnuala M. McAuliffe (Wiley, 2024)
Abstract A breastfeeding‐friendly city is one where there is an enabling environment to support breastfeeding throughout the first 2 years or more of a child's life. Indicators of a breastfeeding‐friendly city have yet to be identified. What are the indicators or criteria used to define breastfeeding friendliness in a geographic area such as a city and the settings within, which we have classified as community, healthcare and workplace? Three major databases and grey literature were searched. Records were screened to identify publications describing criteria such as indicators or descriptions of a breastfeeding‐friendly setting, defined as 'criteria‐sets'. These criteria‐sets were then categorized and summarized by settings. The search up to 2 September 2021 found 119 criteria‐sets from a range of settings: geographic locations (n = 33), community entities (n = 24), healthcare facilities (n = 28), workplaces (n = 28) and others (n = 6). Overall, 15 community, 22 healthcare and 9 workplace related criteria were extracted from the criteria‐sets. Criteria that were consistently present in all settings were policy, training & education, skilled breastfeeding support and physical infrastructure. Some criteria‐sets of geographic locations contained criteria only from a single setting (e.g., the presence of breastfeeding‐friendly cafes). Criteria‐sets were present for all settings as defined in this review, but few were actual indicators. Specifically, there were no existing indicators of a breastfeeding‐friendly city. Several common components of the criteria‐sets were identified, and these could be used in developing indicators of a breastfeeding‐friendly city. Future studies should determine which of these are important and how each can be measured.